Upaya Meningkatkan Kemampuan Guru Dalam Menyusun Rencana Pelaksanaan Pembelajaran Melalui Bimbingan Berkelanjutan Di SMPN 5 Padang Jaya - Rubi’ah Kip Asmoro Ibnu Hadi (Universitas Prof. Dr. Hazairin, S.H, 2017)
The objective of the research is to increase teacher’s competence at SMPN 5 Padang Jaya North Bengkulu in order to make right and complete lesson plan. The method applied in this reasearch is action reasearch in two cycle. Each cycle consist of planning, actuating, observing, and reflecting. The main subject of this reasearch is teachers of SMPN 5 Padang Jaya North Bengkulu. Data collected in this reasearch were analized by individual dialogue, observation, and documentation technique. From the dicussion the researcher got some result, the first cycle achieved value of 69 %, the second cycle achieved 83 %. The result of the research showed that ongoing assistance can increase teacher’s competence in making lesson plan at SMPN 5 Padang Jaya North Bengkulu.